Pengaruh Religiusitas, Altruisme, Empati, dan Norma Subjektif Terhadap Penggunaan ZIS Online pada Gen Z di Surabaya - Aliza Salsa Nabila (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of religiosity, altruism, empathy, and subjective norms on the use of Zakat, Infak, and Sedekah (ZIS) online by Generation Z in Surabaya. Using a quantitative method with an associative approach, the study surveyed 100 respondents from Generation Z who had experience in using online ZIS services. Data analysis was conducted using multiple linear regression with the help of SPSS. The results showed that religiosity, altruism, empathy, and subjective norms significantly influenced the use of online ZIS. This research provides insights into the behavior of tech-savvy Muslim youth and can inform the development of digital zakat services.